Emotion-driven impulsiveness and snack food consumption of European adolescents: Results from the I.Family study. (1st April 2018) - Coumans, Juul M.J.; Danner, Unna N.; Intemann, Timm; De Decker, Annelies; Hadjigeorgiou, Charalambos; Hunsberger, Monica; Moreno, Luis A.; Russo, Paola; Stomfai, Sarolta; Veidebaum, Toomas; Adan, Roger A.H.; Hebestreit, Antje; et al.
Abstract: We aimed to investigate the association between emotion-driven impulsiveness and snack food consumption in 1039 European adolescents aged 12–18 years. During the cross-sectional examination in 2013/2014, complete information was collected on: emotion-driven impulsiveness (using the negative urgency subscale from the Urgency, Premeditation, Perseverance, Sensation seeking, and Positive urgency (UPPS-P) Impulsive Behaviour Scale) and snacking behaviour operationalised as 1) consumption frequency of daily snacks, 2) consumption frequency of energy-dense snacks (both measured using Food Frequency Questionnaire) and 3) usual energy intake of food consumed per snacking occasion in calories. The latter was measured using online self-administered 24-h dietary recalls and was estimated based on the National Cancer Institute (NCI) Method. Anthropometric variables were measured and BMI z-score (zBMI) calculated. Age, sex, highest education level of the family and country of residence were assessed using a questionnaire. Mixed-effect regression analyses were separately conducted for each snacking behaviour outcome with emotion-driven impulsiveness as the exposure. After controlling for zBMI, age, sex, country and socioeconomic status, emotion-driven impulsiveness was positively associated with daily consumption frequency of snacks (β = 0.07, 95% Confidence Interval (CI) [0.02, 0.12]) and consumption frequency of energy-dense snacks (β = 0.25, 95% CI [0.19, 0.31]), but not with usual energy intake of food per snacking (β = 2.52, 95% CI [-0.55, 5.59]). Adolescents with a stronger emotion-driven impulsiveness tendency reported a higher snacking frequency and specifically more energy-dense snacks, whereas the energy intake of snack food seemed less important. These findings have implications for obesity prevention and treatment as they indicate the importance of targeting emotion-driven impulsiveness as a strategy to avoid excessive snacking.